2015
DOI: 10.1093/infdis/jiv569
|View full text |Cite
|
Sign up to set email alerts
|

UropathogenicEscherichia coliEpigenetically Manipulate Host Cell Death Pathways

Abstract: Urinary tract infections caused by uropathogenic Escherichia coli (UPEC) pathovars belong to the most frequent infections in human. It is well established that UPEC can subvert innate immune responses, but the role of UPEC in interfering with host cell death pathways is not known. Here, we show that UPEC abrogates activation of the host cell prosurvival protein kinase B signaling pathway, which results in the activation of mammalian forkhead box O (FOXO) transcription factors. Although FOXOs were localized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Histone acetylation in G. mellonella differed qualitatively (spectrum of histone markers) and quantitatively (level of HAT/HDAC gene expression and abundance of the corresponding modified histones) following infection with the ABU and UPEC strains. The transcriptional induction of HDACs correlates with lower levels of H3 and H4 acetylation, with the exception of H4K5 acetylation, which specifically increased within 1 h of infection with the UPEC strain (40). After 24 h, we observed the hyperacetylation of histone H3K9, supporting similar observations in a mammalian model for Staphylococcus aureus infection (41).…”
Section: Discussionsupporting
confidence: 86%
“…Histone acetylation in G. mellonella differed qualitatively (spectrum of histone markers) and quantitatively (level of HAT/HDAC gene expression and abundance of the corresponding modified histones) following infection with the ABU and UPEC strains. The transcriptional induction of HDACs correlates with lower levels of H3 and H4 acetylation, with the exception of H4K5 acetylation, which specifically increased within 1 h of infection with the UPEC strain (40). After 24 h, we observed the hyperacetylation of histone H3K9, supporting similar observations in a mammalian model for Staphylococcus aureus infection (41).…”
Section: Discussionsupporting
confidence: 86%
“…Quantitative real time PCR (qRT-PCR) was performed as previously described (4,25). The primer sequences are listed in Table I.…”
Section: Quantitative Real Time Pcr Analysismentioning
confidence: 99%
“…Following treatments, cell lysates and immunoblot analyses were performed as previously described (25). The Abs are listed in Table II.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…The prototype RTX poreforming toxin HlyA, frequently encoded by strains of UPEC, has distinct effects on host cells aside from outright lysis (12,13). Although it has been long known that HlyA has proinflammatory, cytolytic, and cytotoxic properties, many recent studies have shown that HlyA can also subvert the innate immune response by suppressing secretion of proinflammatory cytokines and by manipulating host survival signaling pathways, including NF-kB, MAPK, and AKT (12,14,15).…”
mentioning
confidence: 99%